2011
DOI: 10.1074/jbc.m111.251116
|View full text |Cite
|
Sign up to set email alerts
|

An Akt-dependent Increase in Canonical Wnt Signaling and a Decrease in Sclerostin Protein Levels Are Involved in Strontium Ranelate-induced Osteogenic Effects in Human Osteoblasts

Abstract: Sclerostin is an important regulator of bone homeostasis and canonical Wnt signaling is a key regulator of osteogenesis. Strontium ranelate is a treatment for osteoporosis that has been shown to reduce fracture risk, in part, by increasing bone formation. Here we show that exposure of human osteoblasts in primary culture to strontium increased mineralization and decreased the expression of sclerostin, an osteocyte-specific secreted protein that acts as a negative regulator of bone formation by inhibiting canon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 60 publications
6
91
0
Order By: Relevance
“…Finally, both calcium and strontium were found to act on osteoclast precursor cells via the CaSR [34,36]. In addition, strontium, decreased the expression of sclerostin, an osteocyte specific secreted protein that acts as a negative regulator of bone formation by inhibiting canonical Wnt signaling, hence strentium expected to increase canonical Wnt signalling that stimulates osteoblastic proliferation, differentiation and function [37]. Moreover, Gulhan et al [38] showed that the treatment with strontium ranelate for 6 months results in increased serum IGF-1 levels, which may suggest that IGF-1 may be a mediator in the antiresorptive effect of SrRan.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, both calcium and strontium were found to act on osteoclast precursor cells via the CaSR [34,36]. In addition, strontium, decreased the expression of sclerostin, an osteocyte specific secreted protein that acts as a negative regulator of bone formation by inhibiting canonical Wnt signaling, hence strentium expected to increase canonical Wnt signalling that stimulates osteoblastic proliferation, differentiation and function [37]. Moreover, Gulhan et al [38] showed that the treatment with strontium ranelate for 6 months results in increased serum IGF-1 levels, which may suggest that IGF-1 may be a mediator in the antiresorptive effect of SrRan.…”
Section: Discussionmentioning
confidence: 99%
“…This disassociation has also been demonstrated in strontium ranelate treatment. 19 Interestingly, recent data in human osteoblastic cells have suggested that stimulation of Wnt signaling mediates the osteogenic effects of strontium through decreased Sclerostin levels, 20 which is strongly diminished in TG mice. 8 Therefore, these results suggest that potential Sclerostin-targeted therapies 21,22 would not achieve HSC expansion despite their osteogenic actions.…”
Section: Discussionmentioning
confidence: 99%
“…Rp-cAMPs (10-100 µM; Werner et al, 2014;Mangiavacchi and Wolf, 2004;Wang et al, 2012;Pratt et al, 2016;Vallejo and Vallejo, 2002); Ro 31-8220 (1-10 µM; Lee et al, 2013;Montejo-López et al, 2016), PD 98059 (10-50 µM; Sutter et al, 2004;Kim et al, 2008), SP 600125 (20 µM; Hah et al, 2013;Kim et al, 2010) and Akt inhibitor XI (1 µM; Frampton et al,2012;Rybchyn et al, 2011 Inhibitor Cocktail 2). Cell lysates were scraped and clarified by centrifugation at 4°C for 10 min at 14000 x g prior to being assayed for TG activity using the biotin-labeled cadaverine incorporation assay (see below).…”
Section: Cell Extraction For Measurement Of Tg2 Activitymentioning
confidence: 99%